Question:
Solution:
Let us denote by x the blank space in the given equation. Then, we get:
![(7)/(5)-x+(3)/(2)=(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/vttb7me47z6jmbe1r3lsktbcj1omhe2rlf.png)
this is equivalent to:
![(7)/(5)+(3)/(2)-x=(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/538bhllayq9e3ejzuq89vldxg0ebart629.png)
this is equivalent to:
![(14+15)/(10)-x=(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/5ubu3dqiin04qfe4xd5vrw11x6l9f4k4vi.png)
that is:
![(29)/(10)-x=(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/edhfmlshis3weie0ke67cqyw7bkqh70jol.png)
solving for x, we obtain:
![(29)/(10)-(6)/(5)=x](https://img.qammunity.org/2023/formulas/mathematics/college/gfziww0llblu9y2cuzm2r39mlw679dfxe7.png)
that is:
![x=(29)/(10)-(6)/(5)=(29-12)/(10)=(17)/(10)](https://img.qammunity.org/2023/formulas/mathematics/college/8g7jw3kvh65pstta399us86nj1phdqfc2b.png)
so that, the blank space would be:
![(17)/(10)](https://img.qammunity.org/2023/formulas/mathematics/college/3b24nqj0d6joijuvi30vfvzukgpveg8hk0.png)
and the complete expression would be:
![(7)/(5)-(17)/(10)+(3)/(2)=(6)/(5)](https://img.qammunity.org/2023/formulas/mathematics/college/jo6y8woa4onegy4kxnt9utvojw0obv58o8.png)